Evaluasi Fungsi Lurah Dalam Pelayanan Administrasi Kependudukan di Kelurahan Ujungbatu Kecamatan Ujung Batu Kabupaten Rokan Hulu - Setiawan, Kelvin; Rauf, Rahyunir (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
The purpose of this study is to determine the function of the village head in population administration services in Ujungbatu Village, Ujung Batu District, Rokan Hulu Regency. The research method in this study is a qualitative descriptive research method. The types and sources of data used are primary data and secondary data through data collection techniques, namely interviews, observation and documentation. Based on the results of the study, it is known that the function of the Ujungbatu village head in population administration services such as creating SOP in services and making necessary service policies. The Ujungbatu village head has also utilized existing human resources by dividing the tasks and responsibilities of each employee in the village, with the division of tasks for each employee, the services provided will run optimally. Although structurally the Ujungbatu village is to run a bureaucracy, there are still problems such as the bureaucracy that is run tends to be one-way and less responsive to the needs and aspirations of the community, especially the Ujungbatu Village.